ELASTOGRAPHIC EVALUATION OF NATURALLY OCCURING TENDON AND LIGAMENT INJURIES OF THE EQUINE DISTAL LIMB. Issue 6 (25th August 2015) - Lustgarten, Meghann; Redding, W. Rich; Labens, Raphael; Davis, Weston; Daniel, Thomas M.; Griffith, Emily; Seiler, Gabriela S.
Abstract : Compression elastography is an ultrasonographic technique that estimates tissue strain and may have utility in diagnosing and monitoring soft tissue injuries in the equine athlete. Recently, elastography has been proven to be a feasible and repeatable imaging modality for evaluating normal tendons and ligaments of the equine distal forelimb. The purposes of this prospective study were to investigate the ability of elastography to detect spontaneously occurring lesions of equine tendons and ligaments diagnosed with magnetic resonance imaging (MRI) and gray‐scale ultrasound (US) and to characterize the differences in the elastographic appearance of acute vs. chronic injuries. Fifty seven horses with a total of 65 lesions were evaluated. Images were assessed quantitatively and qualitatively. Acute lesions were found to be significantly softer ( P < 0.0001) than chronic lesions ( P < 0.0001) and the stiffness of lesions increased with progression of healing ( P = 0.0138). A negative correlation between lesion hypoechogenicity and softness was appreciated with more hypoechoic lesions appearing softer ( P = 0.0087) and more hyperechoic regions harder ( P = 0.0002). A similar finding occurred with increased signal intensity on short tau inversion recovery (STIR) and proton density (PD) MRI sequences correlating with increased softness on elastography ( P = 0.0164). Using US and MRI as references, commonly encountered soft tissue injuries of the equine distal limb could be detected with elastography. However, elastography was limited for detecting small, proximal injuries of the hindlimb proximal suspensory ligament. Elastographic evaluation of equine tendons and ligaments may allow better characterization of lesion chronicity and severity, and sequential examinations may optimize lesion management, rehabilitation, and return to training.